Antifungal Activity of Cedrol from Cunninghamia lanceolate var. konishii against Phellinus noxius and Its Mechanism - Hsiao, Wen-Wei; Lau, Ka-Man; Chien, Shih-Chang; Chu, Fang-Hua; Chung, Wen-Hsin; Wang, Sheng-Yang (Plants (Basel), 2024)
Phellinus noxius is a highly destructive fungus that causes brown root disease in trees, leading to decay and death. In Taiwan, five prized woods—Taiwania cryptomerioides, Calocedrus macrolepis var. formosana, Cunninghamia lanceolata var. konishii, Chamaecyparis formosensis, and Chamaecyparis obtusa var. formosana—are known for their fragrance and durability. This study aims to explore the anti-brown-root-rot-fungus activity of Cunninghamia lanceolata var. konishii (CL) essential oil (CLOL) and its primary components, while also delving into their mechanisms of action and inhibition pathways. The essential oil (CLOL) from CL wood demonstrated significant efficacy against P. noxius, with an inhibitory concentration (IC50) of 37.5 µg/mL. Cedrol, the major component (78.48%) in CLOL, emerged as a potent antifungal agent, surpassing the reference drug triflumizole. Further assays with cedrol revealed a stronger anti-brown-root-disease activity (IC50 = 15.7 µg/mL) than triflumizole (IC50 = 32.1 µg/mL). Scanning electron microscopy showed deformation and rupture of fungal hyphae treated with CLOL and cedrol, indicating damage to the fungal cell membrane. Cedrol-induced oxidative stress in P. noxius was evidenced by increased reactive oxygen species (ROS) levels, leading to DNA fragmentation, mitochondrial membrane potential reduction, and fungal apoptosis through the mitochondrial pathway. Gel electrophoresis confirmed cedrol-induced DNA fragmentation, whereas TUNEL staining demonstrated increased apoptosis with rising cedrol concentrations. Moreover, protein expression analysis revealed cedrol-triggered release of cytochrome c, activation of caspase-9, and subsequent caspase-3 activation, initiating a caspase cascade reaction. This groundbreaking study establishes cedrol as the first compound to induce apoptosis in P. noxius while inhibiting its growth through oxidative stress, an increase in mitochondrial membrane permeability, and activation of the mitochondrial pathway. The findings offer compelling evidence for cedrol’s potential as an effective antifungal agent against the destructive brown root disease caused by P. noxius.